Catalisadores à base de CuO, Fe2O3 ou CuO-Fe2O3 suportados sobre y-Al2O3, ZrO2 ou ZrO2/y-Al2O3 para a redução de NO com CO - Pires Neto, Nilson do Espírito Santo (2014)
NO, NO2 and N2O nitrogen oxides, named NOx, strongly contribute to the air pollution and to minimize their emissions are used catalytic processes. The catalytic reduction of NO with CO has the advantage to simultaneously abate both pollutants. For that reaction are used noble metal based catalysts, but due to their scarcity and high cost, many research have been established to their substitution by transition metal oxides, which have high potential to catalyze that reaction. Those new catalysts beside to be active to the NO reduction with CO, they must be highly selective to N2 formation, stable at high temperatures and especially resistant to the presence of the interfering compounds (O2, SO2 and H2O). In this work were prepared Fe2O3, CuO or Fe2O3-CuO catalysts supported on y-Al2O3, ZrO2 or ZrO2/y-Al2O3. The supports were prepared via synthesis sol-gel using metallics alkoxides as precursors and the active phases introduced by impregnation of Fe(III) or Cu(II) nitrates. The obtained solids were characterized by X-ray diffraction (XRD), nitrogen adsorption/desorption measurements, hydrogen temperature programmed reduction (H2-TPR) and their activity evaluated by the reduction of NO with CO between 100 to 600°C in the presence or absence of SO2, O2 and H2O. The synthesis via sol-gel resulted in y-Al2O3 and ZrO2/y-Al2O3 supports with high specific surface area that allowed adequately distribute the CuO and Fe2O3 oxides, which did not present X ray diffraction peaks. The catalysts were considerably active in the reduction of NO with CO, with the bimetallic ones being slightly more selective to N2 formation. In the presence of SO2, the Fe2O3/y- Al2O3 and Fe2O3/ZrO2/y-Al2O3 catalysts showed more catalytic stability. The presence of O2 led to a significantly NO conversion loss due to the direct CO oxidation by O2. In the presence of H2O or of all the interfering compounds, the NO conversion loss was more pronounced, except the CuO/ZrO2, that was more resistant in the presence of H2O.